Impact of Processing Parameters and Medium Properties on Escherichia Coli Inactivation in a Continuous Pulsed Electric Field System - Yiting Wang; Farzan Zare; Elisabeth K. Prabawati; Buddhi Dayananda; Mirhojjat Seyedi; Mark S. Turner; Negareh Ghasemi; Firuz Zare; P. Nicholas Shaw; Nidhi Bansal (IEEE Access)
This study investigated the antimicrobial impact of pulsed electric field (PEF) parameters, including pulse number, pulse duration, and high voltage (electric field) levels, in Milli-Q water inoculated with varying loads of Escherichia coli. Milli-Q represents the electrical conductivity of the medium, where keeping the electrical field at a desired value and minimizing conduction current is an ideal environment to analyze pulsed power impacts on bacteria. The maximum log reduction in PEF-treated Milli-Q water was 5.5 log CFU/mL from 8-log CFU/mL initial count after 240,000 pulses (60,000 pulses per step at 9.6 kV). Results showed that increasing the initial count of E. coli from 5 to 7 log CFU/mL lowered the reduction (3.8 vs. 1.5 log CFU/mL, respectively) through PEF treatment, particularly at a lower voltage or electric field. However, further increasing bacterial concentration to 8-log consequently increased the medium conductivity and resulted in higher reductions while the electric field remained constant during the excitation modes. Increasing the conductivity of the treatment medium from 3 to $40~μ $ S/cm using 0.003% saline enhanced the microbial inactivation from 1.5 to 6.6 log CFU/mL under the same PEF conditions with minimal joule heating. Additionally, increasing the pulse number enhanced microbial inactivation, though a maximal point was reached beyond which further pulses did not yield additional inactivation. The study highlights the complexity of multi-objective PEF optimization, which depends on electrical, chemical, and biological parameters. Specifically, the effects of electric field strength vary with voltage adjustments, leading to changes in other factors that affect microbial inactivation.